Aspects of the ARTCP implementation for the Linux kernel 2.6 - I. V. Alexeev; S. A. Merkulov; A. A. Sivov (Моделирование и анализ информационных систем, 2010)
The article secifies the ARTCP header format and describes the algorithm of the ARTCP connection establishment. Some aspects of TCP and ARTCP interaction are discussed. Presented a work plan to implement the ARTCP in Linux.